Determination of Total Phenolic Content of The Stem Bark Extract of Nyirih (Xylocarpus granatum J. Koeing) Using UV - Vis Spectrophotometry Method - Aswar Aswar; Abd. Malik; La Hamidu; Ahmad Najib (Faculty of Pharmacy, Universitas Muslim Indonesia, 2021)
Nyirih is a plant from the Meliaceae family with the Latin name Xylocarpus granatum J.Koeing, this nyirih spreads in tropical waters and does not cluster in certain areas. This study aims to determine the total phenolic content of the stem bark extract of nyirih (Xylocarpus granatum J.Koeing) using the UV-Vis spectrophotometric method. The stem bark extract of nyirih (Xylocarpus granatum J. Koeing) was obtained with maceration method using 96% ethanol solvent. Determination of total phenolic content based on the Folin-Ciocalteau method, where the addition of 7% sodium carbonate provides an alkaline atmosphere that will produce phenolic ions. Furthermore, it will reduce Follin to form a blue complex. At a maximum wavelength of 755 nm, the results showed that the average total phenolic content of the stem bark extract of nyirih (Xylocarpus granatum J. Koeing) was 6.163 mg GAE / g extract.